An efficient method of generating skin fibroblast cells for cell banking - SHARMA, REKHA; SHARMA, HIMANI; AHLAWAT, SONIKA; TANTIA, M S (The Indian Journal of Animal Sciences, 2018)
An optimum cell culture medium is used to generate fibroblast cells for cell banking. Here, we describe a method for obtaining higher number of pure fibroblast cells in much shorter duration from skin tissue explants. Two pronged strategy was used, first two different culture media were selected, one for preferential generation of fibroblast cells in primary culture (Human fibroblast specific media- HifibroXL) and another for their faster multiplication in secondary culture (DMEM + Ham’s F12). Secondly, tissue explants were cultured not only once but up to six times increasing the generation of primary cells per se. This method initially standardized with buffalo (Bubalus bubalis) skin tissue explants works efficiently with camel (Camelus bactrianus) and horse (Equs caballus). Modified cell culture method increases the efficiency of establishing fibroblast cell banks by reducing the cost both in terms of consumables and human effort. It is well suited for today’s fast-paced conservation laboratories.